Alfonso Reyes: demiurge of culture and essays ‘Tierra Firme” (2019)
Decision making is a process that would beinfl uenced by emotional learning, physiologicalstates and proprioceptive experiences. Thus,estrogen levels may affect the selection of riskychoices. To determine it, risk tendency was measuredwith the “Iowa Gambling Task”, in a group of 9women, between 18 and 28 years old, during thethree phases of their menstrual cycle. Signifi cantdifferences were found (p <0.01) in the percentageof risky choices for the fi rst blocks of the task inthe ovulatory phase. Despite the intersubjectivevariability and sample size, this fi nding indicates thathormone levels modulate emotional learning or riskaversion.